“Chicos, Sacad El Móvil De Vuestras Mochilas Porque Lo Vamos A Usar”- Empowering Spanish As Foreign Language Students Through Mobile Devices - Cruz, Mário (2018)
In a post-globalized world, mobiles and tablets are the most popular electronic devices among university students, since they are their first option to access the Internet, exchange messages, take pictures, record videos, play games, etc. Taking into account that they are part of their daily life, it is urgent to take advantage of them to explore learning experiences inside classrooms (Toledo, 2015), by involving students in interactive and gamified tasks (Osores, et al, 2013; Álvarez, 2016; Chou, 2016). Under the scope of a case study related to the learning of linguistic and cultural varieties of Latin-American Spanish (Cruz, 2018; Moreno Fernández, 2010), we will present didactic experiences with digital tools, which were carried out with Spanish as Foreign Language students (A2/B1.2 levels) of the Graduation Degree in Foreign Languages and Cultures at a School of Education in Porto, Portugal. Following a qualitative methodological approach, we have collected and analyzed students’ representations about the use of mobile devices (though questionnaires) and their project works related to the Latin-American Spanish varieties. Results show that students have empowered themselves in the learning process, revealing that they have (re)constructed knowledge related to the topic through hyper sensory strategies and resources (Cruz & Orange, 2016).